An international comparative study of practicum mentors: Learning about ourselves by learning about others. (April 2020) - Clarke, Anthony; Mena, Juanjo
Abstract: Teachers who mentor student teachers on practicum play a critical role in teacher education. However, it is widely reported that these teachers are poorly prepared and lack sufficient knowledge for mentoring. And what is known about mentoring is largely drawn from idiosyncratic single-context studies. In an attempt to extend the scope of this knowledge, this study draws on the Mentoring Profile Inventory (www.mentoringprofile.com ) to chart how mentors conceive of their work within and across six international contexts. The outcome is a comparative analysis that highlights what is 'particular' versus what is 'general' across contexts that has not been previously reported. Highlights: The paper involves mentors from six countries: New Zealand; Thailand; China; Canada; Spain; and Australia. The paper represents a shift from largely idiosyncratic within-context analyses to comparative across-contexts analyses . The paper demonstrates the Mentoring Profile Inventory as a metric for comparative work. The paper highlights distinctive features of mentoring contexts that typically remain hidden within those contexts. The paper demonstrates that there are at least three 'universals' about mentoring regardless of context.